Pengaruh Kompetensi Profesional Dan Motivasi Kerja Terhadap Kinerja Guru Dimoderasi Oleh Lingkungan Kerja (Studi Kasus Guru SMP se-Kecamatan Kandeman Kabupaten Batang) - irna nurnaningsih; Sunarto Sunarto (Faculty of training and education, Pamulang university, 2022)
This study aims to analyze iand test hypotheses about the influence of professional competence and work motivationi teacher performance moderated by the work environment in Junior High School teachers in Kandeman District, Batang Regency. Respondents in this study were junior high school teachers located in Kandeman sub-district, a number of 105 respondents taken from 3 state Junior High Schools and 2 Junior High Schools with private status by using all respondents as samples. The study used questionnaires as a primary data collection method, and used validity tests and reliability tests to test the instruments of each variable studied. Regression Analys is in this study using SPSS software (Statistical Package for the Social Sciences). This study also proves that the results of professional competence and work environment negatively affect teacher performance, while work motivation has no effection to teacher performance. The work environment is able to moderate the influence of professional competence on teacher performance and is not able to moderate the influence of work motivation on the teacher performance of Junior High School teachers in Kandeman District of Batang Regency.Keywords: professional competenc; work motivation; teacher performance; work environment.